Social Care Insurance: A Review of Psychological Influences on Uptake - Ivo Vlaev; Trishna Uttamlal; Laura Kudrna (Frontiers Media S.A., 2020)
There is not currently a developed market for long-term social care insurance in England. Policymakers are interested in what behavioral influences should be considered in the design of insurance products for long-term social care to increase uptake. This review describes the behavioral factors that might be barriers or facilitators of uptake and could be considered in future policy solutions. Behavioral factors include psychological capabilities (knowledge and understanding), which are important given that public knowledge on this topic is poor. Psychological motivations (reflective or automatic biases) may also influence consumers' decision-making. Cultural factors such as language barriers and family norms for caring are considered. Overall, the authors demonstrate processes by which the uptake of long-term social care insurance can be encouraged, pertinent to policymakers.